Case Report: Acute Intracardiac Thrombosis in Children With Coronavirus Disease 2019 (COVID-19) - Bigdelian, Hamid; Sedighi, Mohsen; Sabri, Mohammad Reza; Dehghan, Bahar; Mahdavi, Chehreh; Ahmadi, Alireza; Ghaderian, Mehdi; Rahimi, Hamid; Sadeghizadeh, Atefeh; Emadoleslami, Monirsadat; Mostafavi, Seyed Nasser; Saleh, Rana; et al. (Frontiers in Pediatrics, 2021)
We herein describe a case series of children with SARS-CoV-2 infection (COVID-19) complicated with acute intracardiac thrombosis. The diagnosis of COVID-19 was confirmed through the reverse transcription-polymerase chain reaction (RT-PCR). Transthoracic echocardiography of patients revealed large intracardiac mobile masses resected successfully via cardiac surgery. The underlying mechanisms of this thrombus in the COVID-19 infection may be attributed to the hypercoagulation and inflammatory state of the disease incurred by the SARS-CoV-2 virus.